Human paraoxonase 1 overexpression in mice stimulates HDL cholesterol efflux and reverse cholesterol transport - Ikhlef, Souade (PLoS One, 2017)
This study was aimed to investigate the effect of human PON1 overexpression in mice on cholesterol efflux and reverse cholesterol transport. PON1 overexpression in PON1-Tg mice induced a significant 3-fold (p<0.0001) increase in plasma paraoxonase activity and a significant ~30% (p<0.0001) increase in the capacity of HDL to mediate cholesterol efflux from J774 macrophages compared to wild-type mice. It also caused a significant 4-fold increase (p<0.0001) in the capacity of macrophages to transfer cholesterol to apoA-1, a significant 2-fold (p<0.0003) increase in ABCA1 mRNA and protein expression, and a significant increase in the expression of PPARγ (p<0.0003 and p<0.04, respectively) and LXRα (p<0.0001 and p<0.01, respectively) mRNA and protein compared to macrophages from wild-type mice. Moreover, transfection of J774 macrophages with human PON1 also increased ABCA1, PPARγ and LXRα protein expression and stimulates macrophages cholesterol efflux to apo A1. In vivo measurements showed that the overexpression of PON1 significantly increases the fecal elimination of macrophage-derived cholesterol in PON1-Tg mice. Overall, our results suggested that the overexpression of PON1 in mice may contribute to the regulation of the cholesterol homeostasis by improving the capacity of HDL to mediate cholesterol efflux and by stimulating reverse cholesterol transport.